Pandemic Nightmares: COVID-19 Lockdown Associated With Increased Aggression in Female University Students' Dreams - Kilius, Erica; Abbas, Noor H.; McKinnon, Leela; Samson, David R. (Frontiers in Psychology, 2021)
The COVID-19 pandemic and its associated stressors have impacted the daily lives and sleeping patterns of many individuals, including university students. Dreams may provide insight into how the mind processes changing realities; dreams not only allow consolidation of new information, but may give the opportunity to creatively play out low-risk, hypothetical threat simulations. While there are studies that analyze dreams in high-stress situations, little is known of how the COVID-19 pandemic has impacted dreams of university students. The aim of this study was to explore how the dream content of students was affected during the university COVID-19 lockdown period (March – July, 2020). Using online survey methods, we analyzed dream recall content (n=74) using the Hall-Van de Castle dream coding system and Fisher’s exact tests for sex comparisons. Preliminary results indicate that female students are experiencing more nightmares as compared to male students. Dream analysis found that, relative to normative American College Student (ACS) samples generated pre-COVID-19, women were more likely to experience aggressive interactions in their dream content, including increased physical aggression. Results indicate that university students did experience changes in dream content due to the pandemic lockdown period, with women disproportionally affected. These findings can aid universities in developing support programs for students by bringing forth an understanding of students’ concerns and anxieties as they process the "new normal” of social distancing.